The New Visual Testimonial: Narrative, Authenticity, and Subjectivity in Emerging Commercial Photographic Practice - Morton, Heather (online, 2017)
Abstract: By studying the cultural and aesthetic impact of increasingly pervasive digital technologies and mass amateurization, this paper examines the ramifications of the networked information economy on professional photographic practice and considers the concomitant implications for the photographic classroom. Using the framework of convergence culture as per the writings of Yochai Benkler, Henry Jenkins, Mark Deuze, and Axel Bruns, the impact of accessible and instantaneous image creation and dispersal are explored. Given the rise of consumer engagement in brand co-creation on social media platforms, we can observe massive changes to professional practice in areas such as aesthetics, and the erosion of previous sustainable business models. Indeed, as traditional notions of “expertise” shift from technological prowess to narrative and disseminative abilities, the effects on commercial practice and photographic education need to be addressed. This paper argues that there are three emergin
10.17645/mac.v5i2.809
Keywords: (thesoz)Soziale Medien; (thesoz)Werbung; (thesoz)Marke; (thesoz)Fotografie; (thesoz)Amateur; (thesoz)Verbraucher; (thesoz)Marketing; (thesoz)Ästhetik; (thesoz)Authentizität; (thesoz)Subjektivität; Instagram; brand co-creation; commercial photography; convergent culture; post-secondary education; user generated content